COVID-19 Lockdown and Lifestyle Changes in Saudi Adults With Types 1 and 2 Diabetes - Al-Daghri, Nasser M.; Almiman, Abeer A.; Wani, Kaiser; Khattak, Malak N. K.; Aljohani, Naji J.; Alfawaz, Hanan; Al-Hameidi, Abdulaziz; Aldisi, Dara; Alkhaldi, Ghadah; Sabico, Shaun (Frontiers in Public Health, 2022)
Objective We aimed to evaluate and compare the impact of COVID-19 lockdown on lifestyle changes and other common related effects of the lockdown in Saudi adults with diabetes mellitus (DM), both type 1 (T1D) and type 2 diabetes (T2D). Methods 265 T1D and 285 T2D individuals were included in this cross-sectional survey during lockdown using an online questionnaire and compared with 297 participants without DM. Variables included demographics, treatment changes, use of supplements, change in sleeping habits and physical activity, dietary changes, social and mental health, and education and awareness during COVID-19 lockdown. Results The COVID-19 lockdown was associated with more treatment doses in people with T1D but not in those with T2D (p = 0.003). More participants with T1D and T2D than the control group reported that they felt symptoms of depression during lockdown (ORs of 1.83, p = 0.008 and 2.2, p = 0.001, respectively) and that lockdown affected them psychologically (ORs of 1.64, p = 0.019 and 1.85, p = 0.005, respectively). More participants with T1D than controls reported that their physical activity decreased during lockdown (OR of 2.70, p = 0.024). Furthermore, significantly lesser participants in both DM groups than controls agreed that the health education regarding COVID-19 covered everything (ORs of 0.41, p < 0.001 and 0.56, p < 0.001, respectively for T1D and T2D groups). Regarding dietary habits, the DM groups reported more changes in either the number of daily meals, meal content, or mealtimes than the control group. Conclusions COVID-19 lockdown-associated lifestyle changes were more prevalent in individuals with T1D and T2D compared to control. Findings may assist public health authorities in outlining their responses in pandemics and promote healthy lifestyle adaptations in this high-risk cohort to limit adverse effects in future lockdowns.